Estudo das propriedades farmacológicas e toxicológicas do óleo essencial de cymbopogon winteranus em roedores - Leite, Bárbara Lima Simioni (2012)
The genus Cymbopogon (Poaceae) is composed of more than 100 species found in tropical countries, and about 56 species have essential oils with aromatic characteristics and some ones have mediinal, pharmaceutical and industrial importance. The essential oils of the genus are rich in mono-and sesquiterpenes. Among the species of the genus Cymbopogon winterianus Jowitt, popularly known as |citronella|, |Java citronella| or |jacapé| is used in folk medicine as a repellent, antimicrobial, analgesic, anxiolytic and for the treatment of epilepsy. The aim of this study was to evaluate pharmacological and toxicological properties of the essential oil extracted from the leaves of Cymbopogon winterianus (EOC) in experimental protocols. Analysis by GC-MS showed the major components are citronellal, citronellol and geraniol. In pharmacological screening the main changes observed were: ptosis, sedation and decreased ability to raise. In the test of acute toxicity LD 50 was calculated in 1953.8 mg / kg (1580.9 to 2326.7) (p.o.) and in 567.3 mg / kg (395.8 to 758.2) (ip). The OEC decreased the number of crossings in the test of spontaneous movement and increased the sleep time induced by thiopental. In the the rota-rod task EOC did not interfere the motor coordination of the animals. Antinociceptive, anti-inflammatory and antioxidant effects were performed using the tests of writhing induced by acetic acid, nociception induced by formalin into the paw hot plate, the carrageenan-induced inflammation and sequestering activity of free radicals (DPPH). The results showed that the OEC reduced the response to pain, the migration of neutrophils to the abdominal cavity and is very efficient in sequestering the free radicals. In the evaluation of acute and subchronic toxicity, the animals were treated respectively with EOC in a single dose (900 mg / kg - po) and daily doses of 50mg/kg (po). In the acute test, the main behavioral changes were ptosis, sedation, decreased response to touch, decreased ability to raise and analgesia. No changes suggestive of toxicity in acute and subchronic tests were found in the assessment of body weight, water intake and feed and organ weights. In the evaluation of biochemical parameters, there were significant changes in the dosage of aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase (p <0.05) in both acute and subchronic tests. The results together suggest that EOC possess depressant, antinociceptive, antiinflammatory and antioxidant properties without loss of motor coordination. In addition, EOC showed toxicity, since histological changes were found in kidney and liver in the acute assay and in liver in the subchronic assay.